Toward a Planned Society : From Roosevelt to Nixon. - Graham, Otis L. (Oxford University Press, 1975)
An interpretive, historical account of the concept, major models, and actual practice of national planning in the United States from the Great Depression to the 1970s, with speculation on future developments.